A defesa do direito à educação e o currículo: quando seus caminhos se cruzam - Oliveira, Michele Rodrigues de (2019)
This bibliographic research aims at understanding the propositional contributions of the right to education in the history of Brazilian education and in the movements of organized educators since 1932, associating them to curricular justice, considered as the result of the experience summed up along this process. To achieve this intent, this research scrutinized two concepts: the concept of education as a right and the concept of right to education, both related to the Brazilian reality and found in official documents and the available literature produced in the historic period spanning from the first Brazilian Constitution until the publication of the last PNE - National Plan of Education - (2014-2024). This study resulted in the first chapter. In the second, the research considered the documents written by organized educators in 1932 and 1959 (Manifestos) and in 1986 (Letter of Goiânia). From the analysis of these documents, the study proposes the identification of the principles that strengthened the right to education and shed light onto its actuality. These principles are highlighted in the General Recommendation nº 13, article 13 of the UN International Covenant on Economic, Social, and Cultural Rights. The following chapter brings up the concept of school curriculum originated in the schooling process instituted since the formation of the national states and proceeds discussing the ponderation made in face of that concept by the critical studies about the curriculum. The chapter goes on considering the National Plan of Education (2014 -2024) as the sum up of the experiences in defense of the Brazilian public education and the institutionalization of the culture of participative planning in the country's education, by means of the Education Conferences (CONAE). At this point of the research the National Plan of Education (2014-2024) is related to the school curriculum. The study also discusses the dimensions of curricular justice and its theoretical grounds, social justice and critical theory of curriculum. In its conclusion, the chapter presents the promising entanglements englobing curricular justice - knowledge, co-living and care - and the basic education strategies outlined in the National Plan of Education (2014-2024)